STRATEGI KOMUNIKASI INTERNAL DALAM MENINGKATKAN KINERJA PENGURUS PIMPINAN DAERAH IKATAN PELAJAR MUHAMMADIYAH - Dessy Pratiwi; Hasril Atieq Pohan (Yonetim Jurnal, 2024)
The background of this research is an organization, a social unit and a group of people who have a common goal to achieve success in the organization. Not all organizations always run smoothly, of course there are always obstacles ranging from human resources, form of presence, and in completing their tasks. This research method uses qualitative research objectives using a descriptive approach, data collection techniques through interviews, observation and documentation. The results of this research are from six communication strategy indicators, of which the six indicators have been successful for internal communication strategies in the Regional Leadership of the Palembang City Muhammadiyah Student Association as well as performance indicators including work quality, work quantity, responsibility, initiative and cooperation. The five performance indicators have the results of each indicator, where there is still a lot that needs to be improved in completing the tasks given by top management. The conclusion of this research is that communication strategy and performance development activities can be categorized as successful, namely 50% of the communication strategy and performance indicators